Global political economy - Cohn, Theodore H. 1940- (Pearson Longman, 2012)
Praised for its authoritative coverage, Global Political Economy places the study of IPE in its broadest theoretical context. This text not only helps students understand the fundamentals of how the global economy works but also encourages them to use theory to more fully grasp the connections between key issue areas like trade and development. Written by a leading IPE scholar, Global Political Economy equally emphasizes theory and practice to provide a framework for analyzing current events and long-term developments in the global economy.